The impact of stellar evolution on rotating star clusters: the gravothermal-gravogyro catastrophe and the formation of a bar of black holes. Issue 3 (16th August 2022) - Kamlah, A W H; Spurzem, R; Berczik, P; Sedda, M Arca; Dotti, F Flammini; Neumayer, N; Pang, X; Shu, Q; Tanikawa, A; Giersz, M
ABSTRACT: We present results from a suite of eight direct N -body simulations, performed with nbody6++ GPU, representing realistic models of rotating star clusters with up to 1.1 × 10 5 stars. Our models feature primordial (hard) binaries, a continuous mass spectrum, differential rotation, and tidal mass-loss induced by the overall gravitational field of the host galaxy. We explore the impact of rotation and stellar evolution on the star cluster dynamics. In all runs for rotating star clusters, we detect a previously predicted mechanism: an initial phase of violent relaxation followed by the so-called gravogyro catastrophe. We find that the gravogyro catastrophe reaches a finite amplitude, which depends in strength on the level of the bulk rotation, and then levels off. After this phase, the angular momentum is transferred from high-mass to low-mass particles in the cluster (both stars and compact objects). Simultaneously, the system becomes gravothermally unstable and collapses, thus undergoing the so-called gravothermal-gravogyro catastrophe. Comparing models with and without stellar evolution, we find an interesting difference. When stellar evolution is not considered, the whole process proceeds at a faster pace. The population of heavy objects tends to form a triaxial structure that rotates in the cluster centre. When stellar evolution is considered, we find that such a rotating bar is populated by stellar black holes and their progenitors. The triaxial structure becomes axisymmetric over time, but we also find that the models without stellar evolution suffer repeated gravogyro catastrophes as sufficient angular momentum and mass are removed by the tidal field.